ANALISIS KEBUTUHAN PENGEMBANGAN BAHAN AJAR BERBASIS ETNOSAINS UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN DAN MENANAMKAN NILAI KEARIFAN LOKAL PADA SISWA SDN SUNGAI MIAI 4 - Hosana, Meyta; Nehra, Nor Jannatun; Hasanah, Uswatun; Annur, Syubhan; Sya’ban, Muhammad Fuad (Physics Education Departement, Islamic State University Sulthan Thaha Saifuddin Jambi - Indonesia, 2023)
One of the efforts instilled in local wisdom in children is through science learning in elementary schools. It is expected that teachers will use innovative methods to improve the quality of teaching, and ethnoscience is one such method. To make science lessons more interesting, ethnoscience takes inspiration from regional traditions and beliefs. The purpose of this study is to examine what are the learning needs related to science that elementary school students have. This approach is used to create educational materials that use ethnoscience to integrate science and local wisdom values. One grade 5 teacher and one grade 6 teacher at SDN Sungai Miai 4 served as samples for non-probability sampling techniques. Interviews, documentation, and literature reviews are used to collect data, which is then examined qualitatively descriptively. The following conclusions can be drawn from the results of conversations and data analysis: 1) The teacher can identify the local culture and select material to incorporate into scientific lessons based on it; 2) Books, local environments, audiovisuals, and the internet are examples of learning resources that can be used in ethnoscience lessons; and 3) Teachers can use various methods in ethnoscience learning.